The people speak - White, Michael; Tennessee Indian Council, Inc., Nashville ([Washington : Distributed by ERIC Clearinghouse, 1979)
Since 1976, the Tennessee Indian Council has grown from an idea into an organization staffed by 24 native Americans in 3 offices, administering $500,000 a year, and providing educational, employment, housing, health, and cultural revitalization programs for 8,500 Native American residents of Tennessee. The situation in Tennessee is a microcosm of the Indian world throughout the United States; rural communities experience poverty, lack of education, and lack of job skills, while, in addition, urban Indians face the problems of alienation, alcoholism, and difficulties with jobs and housing. Before the advent of the Council, Indian people (including a sizeable Choctaw population and several Cherokee communities) had no organized voice and virtually no recognition on the state level. The Council is now the only state wide advocate for Indians and Indian programs, standing for the rights of all Native American people, seeking to restore a measure of sovereignty, and operating on the principle of self-determination by responding to the needs of the people as they state them. With funding from CETA, VISTA, Summer Youth Program, and private grants, the Council has operated an employment program resulting in the hiring of 166 persons, 2 GED programs attended by 93 individuals, and provided counseling and referral services for 271 Native Americans. Future plans include the development of a Choctaw bilingual program and a library clearinghouse for historical and contemporary material of Indians of Tennessee and the southeast. (NEC)
Microfiche.
Keywords: American Indian Culture; American Indian Education; American Indians; Delivery Systems; Disadvantaged; Educational Programs; Employment Programs; Federal Aid; Financial Support; Housing; Nonreservation American Indians; Self Determination; Self Esteem; State Programs; Tribes; Tennessee Indian Council Inc; Cherokee (Tribe) -- Choctaw (Tribe) -- Tennessee; Reports, Descriptive